Healthcare Chaplaincy as Specialised Spiritual Care: The Christian Call for Healing in a Global Health Context. Simon Peng-Keller - Newitt, Mark (The journal of theological studies, 2025)
This is a short book, available as a free digital copy, split into three sections: I. Processes of Change and New Circumstances; II. Theological Foundation